A U1 snRNA:pre-mRNA base pairing interaction is required early in yeast spliceosome assembly but does not uniquely define the 5' cleavage site. - Séraphin, B (1988)
We analyzed the effects of suppressor mutations in the U1 snRNA (SNR19) gene from Saccharomyces cerevisiae on the splicing of mutant pre-mRNA substrates. The results indicate that pairing between U1 snRNA and the highly conserved position 5 (GTATGT) of the intron occurs early in spliceosome assembly in vitro. This pairing is important for efficient splicing both in vitro and in vivo. However, pairing at position 5 does not appear to influence 5' splice site selection in vivo, indicating that the previously described U1 snRNA:5' splice junction base pairing interaction is not sufficient to define the 5' cleavage site.